2021
DOI: 10.1128/jvi.00652-21
|View full text |Cite
|
Sign up to set email alerts
|

Marburg and Ebola Virus mRNA 3′ Untranslated Regions Contain Negative Regulators of Translation That Are Modulated by ADAR1 Editing

Abstract: The filovirus family includes deadly pathogens such as Ebola virus (EBOV) and Marburg virus (MARV). A substantial portion of filovirus genomes encode 5’ and 3’ untranslated regions (UTRs) of viral mRNAs. Select viral genomic RNA sequences corresponding to 3’UTRs are prone to editing by ADAR1. A reporter mRNA approach, in which different 5’ or 3’UTRs were inserted into luciferase encoding mRNAs, demonstrates that MARV 3’UTRs yield different levels of reporter gene expression suggesting modulation of translation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…ADAR1 was initially studied as an RNA editing enzyme. For instance, A-to-I editing at the 3′-UTR region of Marburg and Ebola viruses mediated by ADAR1 promoted translation and thus viral replication [ 34 ]. The deaminase domain of ADAR1p110 is critical for facilitating HBV replication [ 20 ], and ADAR1-mediated HBV RNA editing can help the virus evade recognition by the immune system [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADAR1 was initially studied as an RNA editing enzyme. For instance, A-to-I editing at the 3′-UTR region of Marburg and Ebola viruses mediated by ADAR1 promoted translation and thus viral replication [ 34 ]. The deaminase domain of ADAR1p110 is critical for facilitating HBV replication [ 20 ], and ADAR1-mediated HBV RNA editing can help the virus evade recognition by the immune system [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from HDV and MeV, RNA editing has also been reported in several other –ssRNA viruses, such as influenza A virus (IAV) [ 99 , 100 ], dengue virus [ 99 ], lymphocytic choriomeningitis virus (LCMV) [ 101 ], Ebola virus (EBOV) [ 102 ], and Marburg virus [ 102 ]. It was computationally suggested that host-mediated RNA editing is essential for IAV genome replication and viral protein synthesis [ 99 ], exerting a proviral effect by ADAR1p150 to activate the RIG-I (retinoic acid inducible gene I) signaling pathway without deamination [ 100 ].…”
Section: Rna Editing In -Ssrna Virusesmentioning
confidence: 99%
“…Ebola virus belongs to the Filoviridae family, which comprises three genera: Ebolavirus, Marburgvirus, and Cuevavirus [ 12 ]. This virus is a non-segmented, negative-stranded RNA virus, hence, it encodes a non-proofreading RNA-dependent RNA polymerase [ 12 ].…”
Section: Etiology Of Ebola Virus Infectionmentioning
confidence: 99%
“…Ebola virus belongs to the Filoviridae family, which comprises three genera: Ebolavirus, Marburgvirus, and Cuevavirus [ 12 ]. This virus is a non-segmented, negative-stranded RNA virus, hence, it encodes a non-proofreading RNA-dependent RNA polymerase [ 12 ]. Therefore, the absence of proofreading predisposes EBV to higher frequencies of genetic mutations, thus promoting adaptability and expansion of the virus [ 13 ].…”
Section: Etiology Of Ebola Virus Infectionmentioning
confidence: 99%